Kepemimpinan Instruksional dan Strategi Manajerial Kepala Sekolah untuk Meningkatkan Kinerja Guru: Studi Kasus di SMP IT YAPISBA - Ari Suandi; Nazrul Hafizi (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study analyzes the managerial strategies and instructional leadership of the school principal in improving teacher performance at SMP IT YAPISBA Gerunung (Praya, Central Lombok, NTB), focusing on school management functions and mechanisms for teacher performance development as inputs for policy evaluation at the school level.Methods – A qualitative study with a single-case study design. Participants included the principal, vice principal for curriculum, and science and mathematics teachers (n = 4). Data were collected through in-depth interviews, observations of school routines and classroom instruction, and document analysis (teaching tools/modules, attendance and lesson completion records, training evidence, and student achievement).Findings – The findings are organized into four themes: (1) implementation of POAC through planning of teaching instruments, competency-based task allocation, and support via incentives and training; (2) collaborative academic supervision based on monitoring class/teacher attendance and lesson completion, reinforced by periodic evaluation using semester exam results for feedback; (3) professional development through MGMP, Kurikulum Merdeka learning communities, and online training facilitating module development and instructional strategies; (4) student impacts evident in improved discipline and religious habituation, although some students still require remedial instruction and specialized support. Leadership orientation is emphasized through the principle of role modeling: “Leading from the front by setting an example”. Research Implications – Practical implications include competency mapping for training planning, standardization of supervision instruments with follow-up coaching, systematic documentation of measurable performance indicators, and strengthening remedial services and differentiated instruction.